Biomedical polymer hybrid composites - Javad, T.; Dong, Yu; Tang, Y. (Elsevier, 2017)
Bio-based polymer hybrid composites hold a unique position in the fast-growing and active multidisciplinary world of biomaterials where engineers, scientists, and biologists combine their knowledge. It is well known that advances in science and engineering of biomaterials are crucial to solve complex medical and biomedical problems involving replacement, repair, and regeneration of tissues. This chapter covers the definition, importance, categorization, and application of polymer hybrid composites in the biomedical field. It is presented into two main parts. The first part includes the categorization of biomedical polymer hybrid composites, with information about the compositions and specifications of nanocomposites on the basis of hybridization of polymers with natural polymers, biopolymers, minerals, and metals. The second covers biomedical uses of polymer hybrid composites, considering their applications (i.e., drug delivery, tissue engineering, bioadhesion, etc.), and composition.